TOKSISITAS LIMBAH CAIR INDUSTRI BATIK TERHADAP MORFOLOGI SISIK IKAN NILA GIFT (Oreochomis nilotocus) - Riska Andriani; Hartini _ (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2017)
The development of batik industry has increased along with the increasing of society requirement of textile material. Colored liquid in the batik industry has the potential to pollute the environment, so it is necessary research that aims to determine the toxicity of batik industrial waste to morphology of Nila Gift fish (Oreochromis niloticus). The test results of COD content contained in the batik industrial liquid waste is 4951,75 mg/L , analysis of TSS content of batik wastewater showed 448 mg/L, while chromium (Cr) content was 7.0 mg/L, and pH was 6,9. The value of LC-50 96 hours of batik industrial liquid waste is 0.73%, so that the treatment concentration is 0%; 0.37%; 0.46%; 0.55%; 0.64%; and 0.73%. The results showed that the scales exposed directly to batik liquid waste occurred attachment of different substances in each treatment. Treatment with the highest concentration of 0.73% shows the result of attachment of foreign substances that meet the cross section of Nila Gift fish seed scales.